Effects of Phototherapy on Hyperbilirubinemia and Serum Calcium Level in Neonates Admitted in a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2020)
Background: Jaundice is most common problem in neonatal period. It is commonly managed by phototherapy. However, phototherapy may cause hypocalcaemia and create serious complications like convulsion. So, neonatal hyperbilirubinemia associated with hypocalcaemia has increased risk of neurotoxicity.Objective: To determine the effects of conventional single surface phototherapy on serum calcium and serum bilirubin in neonatal hyperbilirubinemia.Methodology: This longitudinal type of descriptive study was conducted in the neonatal unit of Rajshahi Medical College Hospital during January 2016 to December 2017. One hundred forty neonates both term and preterm with jaundice were included into this study. Conjugated hyperbilirubinemia, blood group, Rh incompatibilities, jaundice on 1stday, very LBW babies and very sick neonates were excluded from this study. All neonates were under conventional single surface phototherapy. Total calcium, direct and indirect serum bilirubin were estimated before starting phototherapy and serum calcium level and total bilirubin estimated every 24 hours interval . Results were analyzed statistically by paired student t’ test and z’ test.Results: Total serum bilirubin and calcium level fall significantly and among all groups after phototherapy. Mean SD of serum bilirubin 17.14±4.20 mg/dl before phototherapy and 13.37±3.80 mg/dl after receiving (p